Analysis of Parenting and Involvement of Parents in Early Childhood (Universitas Negeri Semarang, 2019)
The family is the first place for children to gain knowledge. The concept of early childhood education within the family is children’s first education. Therefore family should act as their tutor to make them a high-quality person and grow by their age stages. This study aims to analyze parent’s involvement and parenting in children’s daily life. This parenting model is an actual effort made by the parent to improve children’s learning activities. This parenting model is implemented in the school environment to encourage children to be independent and ready to pursue their education. This study employed a qualitative phenomenological approach and collected the data from observation, interviews, and several documents. The result showed the occurrence of democratic parenting model, in which parents let their children express themselves freely but with certain limitations. Active collaboration between parents and schools through parenting activities in school is proved to be beneficial for both to assess the growth of children in school and children became more engaged in school activities.